THE CORRELATION OF BILINGUALISM (ALBANIAN -TURKISH) WITH THE ACADEMIC PERFORMANCE OF STUDENTS IN PRIMARY SCHOOL - G. Salihu; B. Çibukçiu (Trakia Journal of Sciences)
Purpose: The study "The correlation of bilingualism (Albanian -Turkish) with the academic performance of students in primary school" aimed to extract the most accurate and concrete data on what is the correlation of bilingualism, namely the speaking of the Turkish language in the family in the performance of students at school, in order to contribute to the performance of these children at school. Methods: Since the study model is descriptive, correlational quantitative research method was used.The population of this study were elementary school students who speak Albanian and Turkish in the elementary schools of the municipality of Vushtrri. Results: The results of this study showed the correlation between bilingualism and the performance of bilingual students. Students who learn the Albanian language (mother tongue)first and then the Turkish language (foreign language) have better academic performance, while students who learn the foreign language first (Turkish language) have poorer academic performance in primary school .Conclusions: This study showed the correlation of bilingualism with the academic performance of the students, as well as the preferences and difficulties of bilinguals during schooling.